Living opposite to the hospital of St John : excavations in medieval Northampton 2014 - Brown, Jim, (Archaeopress Archaeology, 2021)
This volume presents the results of archaeological investigations undertaken at a building site in Northampton in 2014. The location was of interest as it lay opposite the former medieval hospital of St. John, which influenced the development of this area of the town.